2016
DOI: 10.1002/ijc.30109
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and effector functions of gamma–delta (γδ) T cells and their therapeutic potential in adoptive cellular therapy for cancer

Abstract: cd T cells are an important innate immune component of the tumor microenvironment and are known to affect the immune response in a wide variety of tumors. Unlike ab T cells, cd T cells are capable of spontaneous secretion of IL-17A and IFN-c without undergoing clonal expansion. Although cd T cells do not require self-MHC-restricted priming, they can distinguish "foreign" or transformed cells from healthy self-cells by using activating and inhibitory killer Ig-like receptors. cd T cells were used in several cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 121 publications
0
75
0
2
Order By: Relevance
“…Although they only constitute less than 5% of all T lymphocytes, their role in the immune system should not be underestimated. γδ T cells have a wide range of functional properties including innate killing, tumor tropism, the support of DC, T cell, and NK cell functions, and, as recently demonstrated, also antigen presentation skills (6467). Moreover, the proportion of CD56 + γδ T cells appears to be determined by their level of activation (6, 20).…”
Section: Cd56 Expression On Human Immune Cells In Health and Diseasementioning
confidence: 97%
“…Although they only constitute less than 5% of all T lymphocytes, their role in the immune system should not be underestimated. γδ T cells have a wide range of functional properties including innate killing, tumor tropism, the support of DC, T cell, and NK cell functions, and, as recently demonstrated, also antigen presentation skills (6467). Moreover, the proportion of CD56 + γδ T cells appears to be determined by their level of activation (6, 20).…”
Section: Cd56 Expression On Human Immune Cells In Health and Diseasementioning
confidence: 97%
“…In this context, immunosuppression mediated by these factors should be considered a physiological response to damage and a drawback of a repair mechanism aimed to maintain tissue homeostasis [2,3,51]. Among the several inhibitory factors secreted by MSC, TGF-β is critical to trigger the generation of both conventional CD4 + Treg and γδ regulatory T cells [52,53]. This indicates that MSC can indeed skew the differentiation/maturation of several effector lymphocytes.…”
Section: Molecular Mechanisms Responsible For the Immunosuppressivmentioning
confidence: 99%
“…γδ T cells are a T cell subset that comprise approximately 5–10 % of all peripheral T cells in healthy individuals [7]. Due to the antitumor function of γδ T cells, they have been proposed to have therapeutic potential for cancer treatment [810]. Several in vivo and in vitro data have demonstrated that γδ T cells are excellent candidates for further improving immunotherapy efficacy because of their intrinsic characteristics and function [11, 12].…”
Section: Introductionmentioning
confidence: 99%